The library research ; the effectiveness of social media on EFL learners speaking skill - Nur, Ardila Angriani; Larekeng, Siti Hajar; Sianna, Sianna (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2021)
ABSTRACT Social media is a tool of information and communication technology used by people to communicate online. There are many kinds of social media such as Facebook, Twitter, Instagram, Youtube, etc. Due to the pandemic in the last two years, students and teachers use virtual or online learning which uses several applications or social media sites. The purpose of this research is to help the EFL learners’ to find out what type of social media is most effectively used for speaking skill. The method used in this study is a qualitative approach with a library research method, there are 15 articles compared in this study with a time span of the last 6 years. The results of this study, based on 15 articles that have been reviewed, show that all types of social media when used in learning English are effective. In this case it is said to be effective based on the type of learning and the skills learned but the researcher found that the most popular social media and most often used by EFL to improve their speaking skill in the last 6 years is the YouTube application.